2018
DOI: 10.1142/s0218488518500095
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the First Twenty-Five Years of the International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems

Abstract: Since the International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems published its first issue in 1993, it has made important contributions to the research field of computer science. In this study, based on the dataset of the publications published in this journal between 1993 and 2016 retrieved from Web of Science, a general overview of this journal is performed using bibliometric methods and visualized networks. First, the productive and influential publications, authors, institutions, count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…The number of co-occurrences and total strength of the co-occurrence links with other keywords for each of the selected keywords were generated in VOSviewer. Cooccurrence is the term used to describe the proximity of keywords in the title, abstract, or keyword list in publication (Van Eck and Waltman [34]) to find connections so that the research topic can be identified (Wang et al [35]). The link indicates the strength of their occurrences.…”
Section: Smart Mobilitymentioning
confidence: 99%
“…The number of co-occurrences and total strength of the co-occurrence links with other keywords for each of the selected keywords were generated in VOSviewer. Cooccurrence is the term used to describe the proximity of keywords in the title, abstract, or keyword list in publication (Van Eck and Waltman [34]) to find connections so that the research topic can be identified (Wang et al [35]). The link indicates the strength of their occurrences.…”
Section: Smart Mobilitymentioning
confidence: 99%
“…Likewise, other studies intended to analyse productivity and impact have been conducted, such as the one on the Journal of Bioscience and Bioengineering [2], that found prolific contributors, a high degree of collaboration, and temporary dynamics of publication. Other techniques emphasising on networks and couplings of bibliometric variables have been reported for the Journal of Uncertainty, Fuzziness and Knowledge-Based Systems [6]. Additional studies in the field of engineering can be found in recent years; for example a paper on the Journal of Cleaner Production [7] characterized different topics were papers published are grouped according to their affinity.…”
Section: Related Workmentioning
confidence: 99%
“…This information is known to two of the authors (CS and SRG) who have participated in the editorial board during the observation frame of the study 6. Information taken from its website, https://revistas.udistrital.edu.co/ojs/index.php/ reving/…”
mentioning
confidence: 99%
“…Yu, Xu, and Fujita (2019) examined the inner structure and the evolution of the Applied Intelligence journal based on bibliometric methods. Using some visualization tools, such as VOSviewer and CiteSpace, many bibliometric research results have been achieved for some journals (Yu, Xu, Pedrycz, & Wang, 2017;Tur-Porcar, Mas-Tur, Merigó, Roig-Tierno, & Watt, 2018;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%